Dysfunctional Immune Regulation in Autoimmune Hepatitis: From Pathogenesis to Novel Therapies - Vuerich, Marta; Wang, Na; Kalbasi, Ahmadreza; Graham, Jonathon J.; Longhi, Maria Serena (Frontiers in Immunology, 2021)
Autoimmune hepatitis (AIH) is a chronic inflammatory disorder characterized by hypergammaglobulinemia, presence of serum autoantibodies and histological features of interface hepatitis. AIH therapeutic management still relies on the administration of corticosteroids, azathioprine and other immunosuppressants like calcineurin inhibitors and mycophenolate mofetil. Withdrawal of immunosuppression often results in disease relapse, and, in some cases, therapy is ineffective or associated with serious side effects. Understanding the mechanisms underlying AIH pathogenesis is therefore of paramount importance to develop more effective and well tolerated agents capable of restoring immunotolerance to liver autoantigens. Imbalance between effector and regulatory cells permits liver damage perpetuation and progression in AIH. Impaired expression and regulation of CD39, an ectoenzyme key to immunotolerance maintenance, have been reported in Tregs and effector Th17-cells derived from AIH patients. Interference with these altered immunoregulatory pathways may open new therapeutic avenues that, in addition to limiting aberrant inflammatory responses, would also reconstitute immune homeostasis. In this review, we highlight the most recent findings in AIH immunopathogenesis and discuss how these could inform and direct the development of novel therapeutic tools.